Nacella magellanica - González-Wevar, Claudio A.; Hüne, Mathias; Rosenfeld, Sebastián; Nakano, Tomoyuki; Saucède, Thomas; Spencer, Hamish; Poulin, Elie (Zenodo, 2018)
NACELLA MAGELLANICA (GMELIN, 1791) (FIG. 4) Patella magellanica Gmelin, 1791: 3703; Reeve, 1854: pl. 10, figs 19A, B; Carcelles, 1950: 52, pl. 1, fig. 12. Patella atramentosa Reeve, 1854: pl. 17, fig. 41A, B. Patella venosa Reeve, 1854: pl. 10, fig. 18A–C. Patella chiloensis Reeve, 1855: pl. 33, fig. 98A, B. Patella meridionales Rochebrune & Mabille, 1885: 109. Patella metallica Rochebrune & Mabille, 1885: 109. Patella pupillata Rochebrune & Mabille, 1885: 110. Patella tincta Rochebrune & Mabille, 1885: 110. Patinella aenea var. magellanica – Pilsbry, 1891: 119, pl. 44, figs 9, 12, 15, 16; pl. 43, figs 1, 6. Patinella magellanica atramentosa – Strebel, 1907: 146, pl. 6, figs 86, 88; pl. 7, figs 91, 92, 94, 95. Patinella aenea var. minor Strebel, 1907: 137, pl. 5, fig. 67a–d. Patinella chiloensis – Strebel, 1907: 151, pl. 7, figs 89, 90. Patinella venosa – Strebel, 1907: 150, pl. 7, fig. 93. Patinigera magellanica – Powell, 1951: 81; Dell, 1964: 273; Castellanos & Landoni, 1988: 22, pl. IV, figs 1, 2. Patinigera chiloensis – Dell, 1964: 273. Patinigera magellanica venosa – Dell, 1964: 273. Nacella ( Patinigera ) magellanica magellanica – Powell, 1973: 198, pl. 73, figs 14, 15; pl. 178, figs 1, 2; Ramírez, 1981: 54; Linse, 1999: 400; Aguirre, 2003: 14; Aguirre, Richiano & Sirch, 2006: 252; Aguirre et al. , 2009: 423. Nacella ( Patinigera ) magellanica venosa – Powell, 1973: 198, pl. 180, figs 3, 4; Ramírez, 1981, 54; Linse, 1999: 400. Nacella magellanica – Guzmán, 1978: 205; Ríos & Gerdes, 1997: 49; Adami & Gordillo, 1999: 186; Ríos & Mutscke, 1999: 196; Bazterrica et al. , 2007: 22; Yoon et al. , 2007: 64; González-Wevar et al. , 2010: 116; 2011a: 1937; 2012a: 448; 2012b: 139; 2017: 863; Aldea & Rosenfeld, 2011: 117; de Aranzamendi, Bastidas & Gardenal, 2011: 2405; 2014: 53; Rosenfeld, Marambio & Aldea, 2013: 11, 2016: 77; Rosenfeld et al. , 2015: 62; 2018: 1; Andrade & Brey, 2014: 65; Andrade et al. , 2016: 2286. Nacella ( Patinigera ) magellanica chiloensis – Ramírez, 1981: 55. Nacella ( Patinigera ) magellanica – Guzman & Rios, 1987: 159; Mutshke et al ., 1998: 8; Reid & Osorio, 2000: 118; fig. 2L–O; Malanga et al. , 2005:551; Valdovinos & Rüth, 2005: 509 (in part), fig. 6A; de Aranzamendi et al. , 2009: 1, fig. 2A–O; Thatje & Rios, 2010: 97. Nacella ( Patinigera ) chiloensis – Valdovinos & Rüth, 2005: 497. Nacella ( Patinigera ) venosa – Valdovinos & Rüth, 2005: 510. Nacella venosa – González-Wevar et al. , 2011a: 1937. Nacella chiloensis – González-Wevar et al. , 2011a: 1937. Nacella magallanica [ sic .] – Ojeda et al. , 2014: 504. Material studied: Puerto Montt; Reloncaví Fjord (41°28’32.78’’ S, 72°55’15.04’’ W) N = 30; Metri, Reloncaví Fjord (41°35’37.30’’ S, 72°42’42.80’’ W) N = 25; Ancud, Chiloé Island (41°53’00.69’’ S, 73°49’52.29’’ W) N = 25; Concoto Island, Pacific Patagonia (44°14’41.60’’ S, 73°37’05.68’’ W) N = 35; Puerto Aguirre, Pacific Patagonia (45°09’57.09’’ S, 73°32’27.07’’ W) N = 25; Costa Channel, Pacific Patagonia (45°48’05.79’’ S, 74°44’28.52’’ W) N = 40; Serrano Channel, Pacific Patagonia (46°26’45.22’’ S, 73°47’44.12’’ W) N = 30; Wager Island, Pacific Patagonia (47°48’’33.22’’ S, 75°00’45.33’’ W) N = 30; Madre de Dios Island, Pacific Patagonia (50°07’09.82’’ S, 75°15’24.79’’ W) N = 20; London Island, Pacific Patagonia (54°40’00.30’’ S, 72°03’58.67’’ W) N = 30; Carlos III Island, Strait of Magellan (53°38’55.41’’ S, 72°15’31.04’’ W) N = 30; Port Famine, Strait of Magellan (53°36’34.07’’ S, 70°55’53.40’’ W) N = 50; Otway Sound, Strait of Magellan (52°56’13.10’’ S, 71°11’39.07’’ W) N = 30; Chabunco, Strait of Magellan (52°59’14.66’’ S, 70°48’44.43’’ W) N = 30; Laredo Bay, Strait of Magellan (52°56’59.14’’ S, 70°48’03.96’’ W) N = 30; Possession Bay, Strait of Magellan (52°13’55.50’’ S, 69°17’50.71’’W) N = 30; Santa María Bay, Tierra del Fuego (53°19’29.86’’ S, 70°22’34.30’’ W) N = 60; Caleta River, Tierra del Fuego (53°51’45.32’’ S, 70°19’54.11’’ W) N = 60; Pía Fjord, Beagle Channel (54°49’36.81’’ S, 69°39’11.31’’ W) N = 40; Garibaldi Fjord, Beagle Channel (54°43’20.63’’ S, 69°57’48.27’’ W) N = 50; Wulaia Bay (54°59’20.30’’ S, 68°09’02.97’’ W) N = 25; Tekenika Bay (55°03’24.66’’ S, 68°07’52.22’’ W) N = 30; Orange Bay (55°27’21.44’’ S, 68°04’02.33’’ W) N = 30; Virginia Bay, Beagle Channel (54°54’16.95’’ S, 67°56’05.35’’ W) N = 30; Puerto Williams, Beagle Channel (54°56’04.95’’ S, 67°36’48.33’’ W) N = 26; Lapataia Bay, Beagle Channel (54°50’58.94’’ S, 68°28’41.95’’ W) N = 30; Hornos Island, Cape Horn (55°58’38.36’’ S, 67°16’36.39’’ W) N = 30; Diego Ramírez Island, Cape Horn (56°30’08.86’’ S, 68°43’38.85’’ W) N = 25; Puerto Deseado, Atlantic Patagonia (47°45’16.17’’ S, 65°52’17.58’’ W) N = 25; Comodoro Rivadavia, Atlantic Patagonia (45°51’52.17’’ S, 67°28’25.50’’ W) N = 26; Hookers Point, Falkland / Malvinas Islands (51°42’09.60’’ S, 57°46’07.49’’ W) N = 50. Shell: The shell shape and sculpture are very variable in this species (de Aranzamendi et al. , 2009; González- Wevar et al. , 2011a) (Fig. 4A–C). The species exhibits a conical morphology, dorsally raised with a very thick and non-translucent shell (Fig. 4A–F). The anterior part of the animal is laterally compressed (Fig 4D–F). The shell is large (maximum length 140 mm), with a high profile. The apex is situated at the anterior 40–50% of the shell’s length (Fig. 4A–F). All the slopes of the shell are convex (Fig. 4A–C). The aperture of the shell is oval. The surface of the shell is sculptured with raised angular primary radial ribs, weaker secondary ones and concentric growth lines across the interspaces. The margin of the shell is highly crenulated. The external coloration of the shell is very variable in the species across its distribution (pale reddish brown, white with dark lines, grey, green and brown). The primary and secondary ribs are brown ash-coloured to dark brown, with clearer interspaces. The internal part of the shell has soft metallic brown coloration with dark lines corresponding to external colour patterns, bordered by a white/brown halo. External anatomy: The ventral area of the foot is light grey and the epipodial fringe is recognizable. The mantle fold is thick and dun-brown coloured. The mantle tentacles are in alternate series of three white shorter and a white longer one and are absent of pigmentation (Fig. 4G). The cephalic tentacles are dorsally pigmented with a black line (Fig. 4G). Radula: See Valdovinos & Rüth (2005) (Fig. 4H). Distribution: Magellanic province. Pacific Patagonia from Chiloé Island to Cape Horn. Atlantic Patagonia from Tierra del Fuego to the Río Negro Province. Falkland/ Malvinas Islands (Fig. 4I). Habitat: High and medium intertidal rocky ecosystem between 0 and 25 m depths. Comments: The species is highly abundant, with a continuous distribution along Pacific Patagonia from Chiloé Island to Cape Horn, including fjords and channels, the Strait of Magellan and Tierra del Fuego, Cape Horn, Hornos Islands and Diego Ramírez Islands (Guzman, 1978; Rios & Gerdes, 1997; Linse, 1999; Reid & Osorio, 2000; Aldea & Rosenfeld, 2011; Gonzalez- Wevar et al. , 2012a; Ojeda et al. , 2014; Rosenfeld et al. , 2015). In the Atlantic, N. magellanica is also highly abundant up north to the Río Negro Province. However, along the Atlantic coast the distribution and abundance of N. magellanica depends on the availability of suitable rocky habitats (Bazterrica et al. , 2007; de Aranzamendi et al. , 2009, 2011, 2014). Similarly, N. magellanica is highly abundant in the Falkland/ Malvinas Islands. Nacella magellanica comprises a single genetic unit throughout Pacific (González-Wevar et al. , 2012a) and Atlantic (de Aranzamendi et al. 2009, 2011) Patagonia, with Falkland/ Malvinas Islands populations detectably different (González-Wevar et al. , 2012a). Molecular and geometric morphometric comparisons showed that N. chiloensis and N. venosa are synonyms of N. magellanica (González-Wevar et al. , 2011a). : Published as part of González-Wevar, Claudio A., Hüne, Mathias, Rosenfeld, Sebastián, Nakano, Tomoyuki, Saucède, Thomas, Spencer, Hamish & Poulin, Elie, 2019, Systematic revision of Nacella (Patellogastropoda: Nacellidae) based on a complete phylogeny of the genus, with the description of a new species from the southern tip of South America, pp. 303-336 in Zoological Journal of the Linnean Society 186 on pages 310-312, DOI: 10.1093/zoolinnean/zly067, http://zenodo.org/record/5718878 : {"references": ["Gmelin JF. 1791. Vermes. In: Gmelin JF, ed. Systema Naturae per Regna Tria Naturae, ed. 13. Leipzig, Germany: Tome 1. G. E. Beer, 3021 - 3910.", "Reeve LA. 1854. Conchologia iconica: on illustrations of the shells of molluscous animals, Vol. VII. Heinietta Street, Covent Garden, London: Lovell Reeve.", "Carcelles AR. 1950. Catalogo de los moluscos marinos de la Patagonia. Anales del Museo del Nahuel Huapi 2: 41 - 99.", "Reeve LA. 1855. Conchologia iconica: on illustrations of the shells of molluscous animals, Vol. VIII. Heinietta Street, Covent Garden, London: Lovell Reeve.", "Rochebrune AT, Mabille J. 1885. Diagnoses de mollusques nouveaux, recueillis par les membres de la mission du Cap Horn et M. Lebrun, preparateur au museum, charge d'une mission a Santa-Cruz de Patagonie. Bulletin de la Societe Philomatique de Paris 7: 100 - 111.", "Pilsbry HA. 1891. Manual of conchology. Structural and systematic with illustrations of the species, Vol. 13. Philadelphia, PA: Academy of Natural Sciences.", "Strebel H. 1907. Beitrage zur Kenntnis der Molluskenfauna der Magalhaen-Provinz. No. 5. Zoologische Jahrbucher, Abteilung fur Systematik, Geographie und Biologie der Tiere 25: 79 - 196.", "Powell AWB. 1951. Antarctic and Subantarctic Mollusca: Pelecypoda and Gastropoda. Discovery Reports 26: 47 - 196.", "Dell, RK. 1964. Marine Mollusca from Macquarie and Heard Islands. Records of the Dominion Museum 4: 267 - 301.", "Castellanos ZJA, Landoni N. 1988. Catalogo descriptivo de la malacofauna marina magallanica 2 Archaeogastropoda. Comision de Investigaciones Cientificas de la Provincia de Buenos Aires (CIC).", "Powell AWB. 1973. The patellid limpets of the World (Patellidae). In: Abbot RT ed. Indo-Pacific Mollusca: monographs of the marine mollusks of the world with emphasis on those of the tropical western Pacific and Indian Oceans, Vol. 3. Auckland, New Zealand: Auckland Institute and Museum.", "Ramirez J. 1981. Moluscos de Chile. Vol. 1 Archeogastropoda. Chile: Museo Nacional de Historia Natural. 1 \u00aa Edicion. Santiago, Chile.", "Linse K. 1999. Mollusca of the Magellan region. A checklist of the species and their distributions. Scientia Marina 63: 399 - 407.", "Aguirre ML. 2003. Late Pleistocene and Holocene palaeoenvironments in Golfo San Jorge, Patagonia: molluscan evidence. Marine Geology 194: 3 - 30.", "Aguirre ML, Richiano S, Sirch Y. 2006. Palaeoenvironments and palaeoclimates of the Quaternary molluscan faunas from the coastal area of Bahia Vera-Camarones (Chubut, Patagonia). Palaeogeography, Palaeoclimatology, Palaeoecology 229: 251 - 286.", "Aguirre ML, Richiano S, Alvarez M, Eastoe C. 2009. Malacofauna Cuaternaria del litoral norte de Santa Cruz (Patagonia, Argentina). Geobios 42: 411 - 434.", "Guzman L. 1978. Patron de distribucion especial y densidad de Nacella magellanica (Gmelin, 1791) en el intermareal del sector oriental del Estrecho de Magallanes. Anales del Instituto de la Patagonia 9: 205 - 219.", "Rios C, Gerdes D. 1997. Ensamble bentonico epifaunistico de un campo intermareal de bloques y cantos en Bahia Laredo, Estrecho de Magallanes. Anales del Instituto de la Patagonia 25: 47 - 55.", "Adami ML, Gordillo S. 1999. Structure and dynamics of the biota associated with Macrocystis pyrifera (Phaeophyta) from the Beagle Channel, Tierra del Fuego. Scientia Marina 63: 183 - 191.", "Bazterrica MC, Silliman BR, Hidalgo FJ, Crain CM, Bertness MD. 2007. Limpet grazing on a physically stressful Patagonian rocky shore. Journal of Experimental Marine Biology and Ecology 353: 22 - 34.", "Yoon SH, Kim W. 2007. 18 S ribosomal DNA sequences provide insight into the phylogeny of patellogastropod limpets (Mollusca: Gastropoda). Molecules and Cells 23: 64 - 71.", "Gonzalez-Wevar CA, Nakano T, Canete JI, Poulin E. 2010. Molecular phylogeny and historical biogeography of Nacella (Patellogastropoda: Nacellidae) in the Southern Ocean. Molecular Phylogenetics and Evolution 56: 115 - 124.", "Gonzalez-Wevar CA, Nakano T, Canete JI, Poulin E. 2011 a. Concerted genetic, morphological and ecological diversification in Nacella limpets in the Magellanic Province. Molecular Ecology 20: 1936 - 1951.", "Gonzalez-Wevar CA, Hune M, Canete JI, Mansilla A, Nakano T, Poulin E. 2012 a. Towards a model of postglacial biogeography in shallow marine species along the Patagonian Province: lessons from the limpet Nacella magellanica (Gmelin, 1791). BMC Evolutionary Biology 12: 139.", "Gonzalez-Wevar CA, Diaz A, Gerard K, Canete JI, Poulin E. 2012 b. Divergence time estimations and contrasting patterns of genetic diversity between Antarctic and southern South America benthic invertebrates. Revista Chilena De Historia Natural 85: 445 - 456.", "Gonzalez-Wevar CA, Hune M, Segovia NI, Nakano T, Spencer HG, Chown S, Saucede T, Johnstone G, Mansilla A, Poulin E. 2017. Following the Antarctic Circumpolar Current: patterns and processes in the biogeography of the limpet Nacella (Mollusca: Patellogastropoda) across the Southern Ocean. Journal of Biogeography 44: 861 - 874.", "Aldea C, Rosenfeld S. 2011. Macromoluscos intermareales de sustratos rocosos de la playa Buque Quemado, Estrecho de Magallanes, sur de Chile. Revista de Biologia Marina y Oceanografia 46: 115 - 124.", "de Aranzamendi MC, Bastida R, Gardenal CN. 2011. Different evolutionary histories in two sympatric limpets of the genus Nacella (Patellogastropoda) in the South-western Atlantic coast. Marine Biology 158: 2405 - 2418.", "de Aranzamendi MC, Bastida R, Gardenal CN. 2014. Genetic population structure in Nacella magellanica: Evidence of rapid range expansion throughout the entire species distribution on the Atlantic coast. Journal of Experimental Marine Biology and Ecology 460: 53 - 61.", "Rosenfeld S, Marambio J, Aldea C. 2013. Comparacion de ensambles de moluscos en dos sustratos intermareales de la cuenca central del Estrecho de Magallanes. Amici Molluscarum 21: 7 - 18.", "Rosenfeld S, Aldea C, Mansilla A, Marambio J, Ojeda J. 2015. Richness, systematics, and distribution of molluscs associated with the macroalga Gigartina skottsbergii in the Strait of Magellan, Chile: a biogeographic affinity study. ZooKeys 519: 49 - 100.", "Andrade C, Brey T. 2014. Trophic ecology of limpets among rocky intertidal in Bahia Laredo, Strait of Magellan (Chile). Anales Instituto Patagonia 42: 65 - 70.", "Andrade C, Rios C, Gerdes D, Brey T. 2016. Trophic structure of shallow-water benthic communities in the sub-Antarctic Strait of Magellan. Polar Biology 39: 2281 - 2297.", "Guzman L, Rios CF. 1987. Age and growth of the Subantarctic limpet Nacella magellanica magellanica (Gmelin, 1791) from the Strait of Magellan, Chile. The Veliger 30: 159 - 166.", "Reid DG, Osorio C. 2000. The shallow-water marine Mollusca of the Estero Elefantes and Laguna San Rafael southern Chile. Bulletin of the Natural History Museum of London (Zoology) 66: 109 - 146.", "Malanga G, Estevez M, Calvo J, Abele D, Puntarulo S. 2005. Oxidative stress in gills of limpet from the Beagle Channel: comparison with limpets from the Antarctic. Scientia Marina 69: 297 - 304.", "Valdovinos C, Ruth M. 2005. Nacellidae limpets of southern South America: taxonomy and distribution. Revista Chilena de Historia Natural 78: 497 - 517.", "de Aranzamendi MC, Gardenal CN, Martin JP, Bastida R. 2009. Limpets of the genus Nacella (Patellogastropoda) from the Southwestern Atlantic: species identification based on molecular data. Journal of Molluscan Studies 75: 241 - 251.", "Thatje S, Rios C. 2010. Subantarctic limpet populations today and human impact about 1400 years ago. Anales Instituto de la Patagonia 38: 97 - 102.", "Ojeda J, Rosenfeld S, Marambio J, Rozzi R, Mansilla A. 2014. Patrones estacionales y espaciales de la diversidad de moluscos intermareales de bahia Robalo, canal Beagle, Reserva de la Biosfera Cabo de Hornos, Chile. Revista de Biologia Marina y Oceanografia 49: 493 - 509."]}